(untitled) (Phenomenology, Humanities and Sciences, 2023)
Phenomenological interviews are robust in that they provide a rich narrative and descriptive details. Participants play the role of storytellers. The challenge is figuring out how to involve them in the process. Davidson answers the question, "Why not just ask participants what an experience is like for them?" helping readers to think about which questions help elicit rich narratives and the importance of the experience’s context. With examples and suggestions of principles that help the researcher, this chapter illustrates ways that encourage each participant to elaborate their experience in a detailed way, listening and building a scenario in which, invariably, narratives will flow.